Teachers’ research training in Medical Sciences - Liyipsi Abreu Martín; Arturo Prudencio Puga García; Eduardo Veloso Pérez; Yennia Coca Pérez; Ignacia Rodríguez Estévez; Milayda Victoria Rodríguez Soto (Medisur)
Foundation: Higher Medical Education in Cuba has the challenge of training qualified, competent professionals, committed to current social development and capable of managing their own knowledge. Knowing the teachers’ research training allows us to design strategies to modify and elevate scientific research activity in medical sciences. Objective: to describe the teachers’ research training of Basic Biomedical Sciences in the Medicine program at the Sancti Spíritus Medical Sciences University. Methods: a retrospective cross-sectional descriptive study was carried out from January 2022 to July 2024, at the Sancti Spíritus Medical Sciences University. Documentary review, interviews and surveys of 44 teachers of Basic Biomedical Sciences were used. The measured variables were: scientific results, scientific production, participation in research, scientific events and research projects. Results: In the studied universe graduates in Medicine predominate, 38 teachers (86.3%), and the transitional category of instructor 21 teachers (47.7%). In the attitudinal dimension, teachers stand out in the effective category (36.3%); in the cognitive and procedural dimension, they do not indicate ineffectiveness for knowledge management and development of research skills; in the total analysis of the result, the acceptable category predominates (59.0%). Conclusions: Basic Biomedical Sciences teachers in the Medicine course at the Sancti Spíritus Medical Sciences University do not present a research training that favors scientific and research activity from educational research.